The Arizona Electronic Atlas: A New Reference Instructional Tool - Jeanne Pfander; Danielle Carlock (Issues in Science and Technology Librarianship)
The growth of geographic information systems (GIS) technology within academic disciplines has been mirrored in the past decade within libraries. The Association of Research Libraries (ARL) GIS literacy project, initiated in 1992, is widely regarded as the impetus for the spread of GIS-related services in academic libraries. Libraries have utilized a wide range of approaches, from setting up single dedicated GIS workstations to establishing GIS labs and creating positions for a GIS specialist. Taking the idea of GIS services one step further, the University of Arizona Libraries has created the Arizona Electronic Atlas -- an innovative, web-based interactive mapping resource that allows users to create, manipulate and download accurate and current maps and data. This paper describes the background and development of the Atlas, as well as its reference and instructional applications.